Law As Innovation Driver: Analyzing The Influence Ofintellectual Property Rights On Indonesia’s Start-Up Growth - Evelyn, Evelyn; Lie, Gunardi (Jurnal Ilmiah Wahana Pendidikan, 2025)
Intellectual Property Rights refer to the legal protection given to creators/innovators over their creations/inventions. It is given to them for the protection of their work from unlawful imitation or infringement and also for misuse. Intellectual property rights also give appreciation to the creator. This appreciation could be either in the form of recognition of the produced work or acknowledgment. Not only appreciation but also these Intellectual Property Rights provide financial benefits to the creators of the work. The Intellectual Property Rights support startups to continue innovating. With the IPR in place, it is indicative that startup companies will be challenged and be propelled to create new works from their innovations for the advancement of Indonesia's economy. This research aims to find out the meaning of IPR policies on the development of startups in Indonesia from the regulatory, implementation, and law enforcement aspects. This observation of the study has pointed out that though theoretically robust Intellectual Property Rights (IPR) laws support innovation, yet in challenges rising from law enforcement and awareness about IPR, often create problems for the full realization of the policy. The following recommendations for policy: strengthening the improvement of legal infrastructure and education on the Intellectual Property Rights (IPR) with the view of supporting a strong basis for innovation and the development of startup companies in Indonesia. In turn, this will enhance economic development in the country.